2007
DOI: 10.1007/s00244-006-0074-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Mannan on the Toxicity Produced in Mice Fed Aflatoxin B1 Contaminated Corn

Abstract: Aflatoxin B(1) (AFB(1)) is a potent mutagenic and carcinogenic agent found in numerous agricultural and dairy products consumed by humans. Therefore, we evaluated the capacity of mannan to cope with its genotoxic potential. We prepared a diet constituted of corn (90%) plus the recommended amount of other nutrients, as well as with the tested compounds (mannan and/or AFB(1)). Mice were fed this diet during 4 weeks as follows: one group with AFB(1)-contaminated corn (0.25 mg/kg of corn), three groups with mannan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Control and S. cerevisiae-fed mice had a low MNNE rate, whereas mice fed only with AFB1 showed a significant MNNE increase. The same authors conducted a similar study in which they treated mice with AFB1-contaminated corn (0.25 mg/kg of corn) and mannan (50-500 mg/kg) instead of dosing with S. cerevisiae (Madrigal-Santillán et al, 2007). The results demonstrated an antigenotoxic effect of this component of the yeast wall, with the best response found in mice fed with AFB1 plus 500 mg/kg of mannan.…”
Section: Mycotoxinsmentioning
confidence: 93%
“…Control and S. cerevisiae-fed mice had a low MNNE rate, whereas mice fed only with AFB1 showed a significant MNNE increase. The same authors conducted a similar study in which they treated mice with AFB1-contaminated corn (0.25 mg/kg of corn) and mannan (50-500 mg/kg) instead of dosing with S. cerevisiae (Madrigal-Santillán et al, 2007). The results demonstrated an antigenotoxic effect of this component of the yeast wall, with the best response found in mice fed with AFB1 plus 500 mg/kg of mannan.…”
Section: Mycotoxinsmentioning
confidence: 93%
“…Two blood smears were made from the tail of each animal, fixed in methanol for 5 min and stained for 20 min with a 4% Giemsa solution made in phosphate-buffered saline, at a pH of 6.8 [18]. One thousand erythrocytes per animal were scored to determine the rate of MNPE.…”
Section: Methodsmentioning
confidence: 99%
“…Man in particular, is a highly branched oligosaccharide constituted by a main chain of mannoses linearly joined through α-1–6 bonds, and with α-1–2 and 1–3 bonds in the branches. In an earlier report we showed that the administration of Man for four weeks to mice fed with AFB 1 contaminated corn reduced the frequency of micronuclei and SCE about 70 % [ 11 ]. Other authors have demonstrated a significant in vitro antimutagenic effect of the compound by reduction of the damage induced by ofloxacin and acridine orange in the chloroplast DNA of Euglena gracilis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%